Analysis of Legal Protection of Investors in Capital Markets: Perspective of Law No. 8 of 1995, Law No. 21 of 2011, and Law No. 11 Year 2020 - Made Sinta Syaharani Sujana (Jurnal Hukum Prasada, 2024)
Legal protection is a key element in strengthening aspects of law enforcement in a country, including in the economic and legal fields. This protection involves the interests of investors, for which investment law in a country must include regulations to protect investors and their invested capital. This research examines the legal protection of investors in the Indonesian capital market with reference to Law No. 8 of 1995 concerning the Capital Market, Law No. 21 of 2011 concerning the Financial Services Authority (OJK), and Law No. 11 of 2020 concerning Job Creation. The research method used is normative juridical with a statute approach and conceptual approach. The problem formulations in this study are: (1) How is the effectiveness of legal protection for investors based on the provisions of Law No. 8 of 1995 and Law No. 21 of 2011? (2) What significant changes does Law No. 11 of 2020 bring to the investor protection mechanism and its impact? This study found that Law No. 8 of 1995 and Law No. 21 of 2011 have provided a comprehensive legal framework for investor protection, but Law No. 11 of 2020 brought a number of changes that affect capital market regulation and investor protection. These changes, including regulatory adjustments and strengthened supervision, are expected to improve investor protection. This research emphasizes the importance of consistent implementation and effective law enforcement to achieve the goal of optimal legal protection.